2008
DOI: 10.1089/ast.2007.0134
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Rock Inhabitants Survive Hypervelocity Impacts on Mars-Like Host Planets: First Phase of Lithopanspermia Experimentally Tested

Abstract: The scenario of lithopanspermia describes the viable transport of microorganisms via meteorites. To test the first step of lithopanspermia, i.e., the impact ejection from a planet, systematic shock recovery experiments within a pressure range observed in martian meteorites (5-50 GPa) were performed with dry layers of microorganisms (spores of Bacillus subtilis, cells of the endolithic cyanobacterium Chroococcidiopsis, and thalli and ascocarps of the lichen Xanthoria elegans) sandwiched between gabbro discs (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 63 publications
6
152
1
3
Order By: Relevance
“…Despite this extremely challenging situation for life, there are organisms on Earth which are potentially able to survive space travel: it has been shown that different micro-organisms can survive launch by spallation from a hypervelocity impact (Horneck et al 2008a;Fajardo-Cavazos et al 2009) and hypervelocity atmospheric transit (Fajardo-Cavazos et al 2005). Thus, it has been suggested that, for example, bacterial spores situated on or within meteorites could survive interplanetary transport (Fajardo-Cavazos et al 2009) and hypervelocity entry from space through Earth's atmosphere (Fajardo-Cavazos et al 2005;reviewed in Olsson-Francis & Cockell 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this extremely challenging situation for life, there are organisms on Earth which are potentially able to survive space travel: it has been shown that different micro-organisms can survive launch by spallation from a hypervelocity impact (Horneck et al 2008a;Fajardo-Cavazos et al 2009) and hypervelocity atmospheric transit (Fajardo-Cavazos et al 2005). Thus, it has been suggested that, for example, bacterial spores situated on or within meteorites could survive interplanetary transport (Fajardo-Cavazos et al 2009) and hypervelocity entry from space through Earth's atmosphere (Fajardo-Cavazos et al 2005;reviewed in Olsson-Francis & Cockell 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A more deleterious stressor of organisms during the process of impact ejection is shock. Spores of Bacillus subtilis can survive shock pressures greater than 50 GPa (Burchell et al 2001(Burchell et al , 2004Horneck 2001a;Stöffler et al 2007;Horneck et al 2007), which would allow for the survival of ejection to Earth's escape velocity. In contrast, vegetative cells are susceptible to disruption by low shock pressures.…”
Section: Launch Of Photosynthesis From a Planetmentioning
confidence: 99%
“…In flyer-plate experiments, we have shown that the asporogenous phototrophic cyanobacterium Chroococcidiopsis sp. was killed at shock pressures greater than 10 GPa Horneck et al 2007). This organism was chosen because it is naturally endolithic.…”
Section: Launch Of Photosynthesis From a Planetmentioning
confidence: 99%
“…40, 1665-1671. Horneck et al (2008). Microbial rock inhabitants survive hypervelocity impacts on Mars-like host planets: First phase of Lithopanspermia experimentally tested, Astrobiology, 8: 17-29.…”
Section: Dynamics Of Pattern Formation In Biomimetic Systemsmentioning
confidence: 99%
“…But did it occur on Earth? As Earth was sterilized during the LHB, about 700 My after the formation of the solar system, seeding by lithopanspermia is a definite possibility (Horneck et al, 2008). If so, the question is what the place of origin could be in the solar system.…”
Section: On the Transfer Of Meteorites (And Life?) From Earth To The mentioning
confidence: 99%